Pathophysiologic mechanisms in septic shock - King, Elizabeth G (Lab Invest, 2013)
The systemic inflammatory response that occurs in the septic patient as a result of an infectious insult affects multiple organs and systems, causing numerous physiological derangements. Alterations in phagocytic, lymphocytic and endothelial cell function and immune regulation are evident, leading to heterogeneity in a host’s response to a septic challenge. In addition, the normal hemostatic balance shifts toward a procoagulant state through alterations in tissue factor, antithrombin, protein C and the inhibition of fibinolysis, which can result in thrombus formation and paradoxical hemostatic failure. In an effort to diagnose sepsis and predict outcomes, biomarkers such as C-reactive protein, pro-calcitonin, pro- and anti-inflammatory cytokines have been investigated with varying results. Targeted therapies for sepsis, most notably Xigris (recombinant human activated protein C), have proven unsuccessful and treatment continues to remain reliant on source control, antibiotics and supportive interventions, specifically early goal-directed therapy. This brief review gives an overview of the immunopathologic and coagulopathic alterations that occur in sepsis, soluble inflammatory mediators as potential diagnostic and prognostic biomarkers, and the clinical management of the septic patient.